(untitled) (Al-Academy, 2019)
The images and drawings reduce the intellectual, symbolic and cognitive dimensions inside them that make them an intermediary that imposes itself on the educational method, as they have become responsive to all the needs of the student in the modern era unlike the previous periods. The artistic direction of the illustrations in the scientific books meets the educational and pedagogical needs of the learner and their frame in an illustrative educational method that contributes in developing the student’s abilities to benefit from the scientific curricula in the age of scientific and cognitive development. Here, the researcher finds that the artistic direction of the illustrations lacks the achievement of scientific and technical performance, as it did not rise to the design level to cope with the scientific developments in the modern era, which urged the researcher to study (the reality of the artistic direction of illustrations in the textbooks) of physics for the third intermediate stage as a model for the study and for the importance of the studying stage. The theoretical framework includes the first topic about (the artistic direction of illustrations), and the second section dealt with (the methods of the artistic direction of illustrations), and after the analysis, the researcher reached a set of results, the most important of which are: The artistic direction methods were used without taking in account the controls and specifications of the direction methods in terms of employing the design foundations and elements of the sample drawings. The use of ready-made drawings and designs from the Web sites with a clear accuracy, making the samples a reality employed in the textbook. Then the scientific conclusions in which the set objectives have been achieved are listed